The girl who chased away sorrow : the diary of Sarah Nita, a Navajo girl - Turner, Ann Warren (New York : Scholastic, 1999)
The deeply affecting story of a Navajo girl on the long walk from their home in northern Arizona to Fort Sumner in Eastern New Mexico.
"New Mexico, 1864"--Cover.
920
Accelerated Reader AR
Keywords: Navajo girls -- Social conditions -- Juvenile literature; Navajo Indians -- Relocation -- Juvenile literature; Navajo Indians -- History -- Juvenile literature; Navajo girls -- social conditions -- Fiction; Navajo Indians -- Relocation -- Fiction; Navajo Indians -- History -- Fiction; Diaries -- Fiction